Miscut measuring of SrTiO3 single crystal using high resolution X-ray diffraction - Abdullah, Aziz M.; Saeed, Salah R. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Strontium titanate (SrTiO3) is one of the perovskite type metal oxides with multifunctional properties and it has a lot of applications in various sectors of technology. In this paper, we obtained the miscut angles from Bragg peak after performing ω scans of HRXRD at different angles of φ with intervals of 90○. The obtained results located between 0.2015○ and 0.4302○ using two ways (mathematically and Epitaxy software), which is considered as a tolerance limit (less than 1°) to cut the substrates.
Keywords: Strontium titanate SrTiO3 High resolution Xray diffraction Substrate Thin films Miscut